THE INFLUENCE OF MARKETING MIX ON PURCHASING DECISIONS (STUDY OF KALIKA PROPERTY CONSUMERS IN PURBALINGGA) - Puspitaningtias, Rofi; Afriani, Lita Ningrum; Sofyan, Is’wara (Program Studi Manajemen Fakultas Ekonomi Universitas Palembang, 2025)
. The main factors that influence home purchases include the need for a comfortable place to live, strategic location, adequate facilities, and ease of financing such as Home Ownership Credit (KPR) The need for a house is often considered a profitable long-term investment because the value of the property tends to increase The decision to buy a house requires comprehensive consideration, including price, location, building quality, and access to public facilities Therefore, developers need to understand community preferences in order to offer products that suit market needs This study aims to determine how the marketing mix influences products, prices, promotions and places on purchasing decisions of Kalika Property consumers in Purbalingga Regency This study uses a quantitative approach with data sources derived from questionnaires given to Kalika Property Consumers in Purbalingga Regency with a total of 75 respondents This study uses smartPLS 3 as a data analysis and the results of this study indicate that products, prices and promotions have a significant positive effect on purchasing decisions but places have a negative and insignificant effect on purchasing decisions.